E-module in Learning Mathematics: An effort to Stimulate Learning Independence - Netriwati, Netriwati; Tricia, Ami; Gunawan, Wawan; Nendra, Fadly (CV FOUNDAE, 2022)
The use of technology in education results in user-friendly, distinctive, valuable, and informative learning apps. MIT App Inventor was used in this development research to create a valid and interesting junior high school mathematics learning module. The ADDIE model was used to conduct this development research. To assess the product's feasibility, validation was performed by media and material experts. Product trials were conducted by analyzing students' answers to establish the product's attractiveness. This study's test subjects were 45 UIN Raden Intan Lampung students majoring in Mathematics Education in semester 1. The feasibility test results from media and material validators were 3.32 and 3.52 in the valid category. The attractiveness test received a score of 3.54 on the small-scale trial with the highly attractive and 3.6 on the large-scale trial with the same criteria. It is possible to conclude that the developed module is feasible.